2022
DOI: 10.1186/s10195-022-00674-3
|View full text |Cite
|
Sign up to set email alerts
|

The semi-extended infrapatellar intramedullary nailing of distal tibia fractures: a randomized clinical trial

Abstract: Background Malalignment is a common event during the intramedullary nailing (IMN) of distal tibia fractures (DTFs). Although it is reported that the semi-extended IMN techniques such as suprapatellar (SP) and parapatellar (PP) approaches may be superior in preventing malalignment, the application of these techniques is concerning owing to the intra-articular involvement. We thus developed an extra-articular semi-extended infrapatellar (SEIP) approach which utilizes the infrapatellar (IP) space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The overall complication rate after repositioning with a scarf clamp was 37%, while the overall complication rate after triangular anchor repositioning was 7%, with a signi cant difference between the two groups (P < 0.05). However, interestingly, the various complications were not signi cantly different between the two groups (P > 0.05), which was also reported in a study by Lu et al [14] . Therefore, the use of triangular anchor repositioning forceps can reduce the incidence of complications after intramedullary nailing for long oblique or spiral distal tibial fractures and greatly improve the outcome of intramedullary nailing.…”
Section: Discussionsupporting
confidence: 85%
“…The overall complication rate after repositioning with a scarf clamp was 37%, while the overall complication rate after triangular anchor repositioning was 7%, with a signi cant difference between the two groups (P < 0.05). However, interestingly, the various complications were not signi cantly different between the two groups (P > 0.05), which was also reported in a study by Lu et al [14] . Therefore, the use of triangular anchor repositioning forceps can reduce the incidence of complications after intramedullary nailing for long oblique or spiral distal tibial fractures and greatly improve the outcome of intramedullary nailing.…”
Section: Discussionsupporting
confidence: 85%
“…However, it has not been reported in existing evidence. Lu et al [ 26 ] demonstrated another semi-extended nailing technique using an infrapatellar extraarticular approach that does not require the dissection of the retinaculum, thus eliminating the chance of patellar instability. Nonetheless, nailing using this approach requires a newly designed intramedullary nail and special instrument, which might limit the routine use of this approach.…”
Section: Discussionmentioning
confidence: 99%